The dead center [videorecording (DVD)] - Carruth, Shane; Child, Jeremy; Jagannathan, Poorna, 1972- (Arrow Video, 2019)
When a very dead suicide victim disappears from the morgue, it sets in motion a chain of events that has the power to immolate everything, and everyone, it touches.